Utilization of Palm Oil Mill Effluent (POME) Liquid Waste to Increase Density and Growth Rate of Microalgae Chlorella Pyrenoidosa - Welmar Olfan Basten Barat; Srinatalia Silaen; Ewin Handoco S (Journal of Applied Geospatial Information, 2023)
Microalgae Chlorella pyrenoidosa is a microalgae that has the potential to have various roles, especially as a bioabsorbant for organic waste. The growth of the oil palm plantation industry is also directly proportional to the increase in waste generated from the CPO production process, namely POME Waste (Palm Oil Mill Effluent). POME waste has a high nutrient content so that it can be utilized by the microalgae Chlorella pyrenoidosa. This study aims to utilize POME waste to increase the growth of Chlorella pyrenoidosa. Microalgae cultivation had a significant effect on the 1:2 treatment and 1:3 treatment when compared to the control cultivation medium with the highest cell density values ​​of 263(106cells/ml) and 279(106cells/ml) respectively. Injection of POME waste into microalgae rearing media will have an impact on increasing the growth of Chlorella pyrenoidosa microalgae.